2014
DOI: 10.1051/0004-6361/201423832
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from stellar rotation of enhanced disc dispersal

Abstract: Context. The early stage of stellar evolution is characterized by a magnetic coupling between a star and its accretion disc, known as a star-disc locking mechanism. The disc-locking prevents the star to spin its rotation up, and its timescale depends on the disc lifetime, which should not be longer than about 10 Myr. Some mechanisms can significantly shorten this lifetime, allowing a few stars to start spinning up much earlier than other stars and increasing the observed rotation period dispersion among coeval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Moreover, when a star has a companion in a close orbit, the rotation period allows us to shed light on the early stage of its stellar evolution, specifically on the primordial disc lifetime. In fact, the faster rotation that we observe in a close binary with respect to an equal-mass single star reveals that gravitational effects have enhanced the disc dispersal, and shortened the disc-locking duration (see, e.g., Messina et al 2014Messina et al , 2015aMessina et al , 2016a. The rotation period combined with the v sin i can put constraints on the value of the stellar radius since the inclination of the stellar rotation axis must be i < 90…”
Section: Introductionmentioning
confidence: 68%
“…Moreover, when a star has a companion in a close orbit, the rotation period allows us to shed light on the early stage of its stellar evolution, specifically on the primordial disc lifetime. In fact, the faster rotation that we observe in a close binary with respect to an equal-mass single star reveals that gravitational effects have enhanced the disc dispersal, and shortened the disc-locking duration (see, e.g., Messina et al 2014Messina et al , 2015aMessina et al , 2016a. The rotation period combined with the v sin i can put constraints on the value of the stellar radius since the inclination of the stellar rotation axis must be i < 90…”
Section: Introductionmentioning
confidence: 68%
“…When available, we gathered masses of single early type stars and close binaries from the literature (e.g., Strassmeier & Rice 2000;Neuhäuser et al 2002;Caballero 2009;Donati et al 2011;Janson et al 2012;Elliott et al 2015;Montet et al 2015) or suitable information that allowed us to make a precise derivation (e.g., magnitude differences from adaptive optics or lucky imaging, mass ratios from spectroscopic monitoring - Chauvin et al 2010;Neuhäuser et al 2011;Janson et al 2012;Messina et al 2014;Bowler et al 2015;Elliott et al 2015). Masses range approximately from 2.4 M for η Tel A to well below the substellar boundary for L 186-67 B with a broad maximum of the distribution at 0.5-1.0 M .…”
Section: Notesmentioning
confidence: 99%
“…Derived masses reasonably match those expected from spectral types, when available. For the sake of completeness, we also list spectral types compiled from a number of sources in Table A.5 (Riaz et al 2006;Reid et al 2007;Pickles & Depagne 2010;Janson et al 2012;Kraus et al 2014;Messina et al 2014;Rodríguez et al 2014;Mason et al 2015;I. Gallardo & M. Gómez Garrido, priv.…”
Section: Notesmentioning
confidence: 99%
“…Despite these difficulties, some studies suggest that the connection between age, rotation, and activity may also hold in early-M dwarfs (e.g. Delfosse et al 1998;Messina et al 2003;Mohanty & Basri 2003;Pizzolato et al 2003;West et al 2004;Kiraga & Stepien 2007;Browning et al 2010;Reiners et al 2012;Stelzer et al 2013b;West et al 2015), although deviations in the case of close M binaries have been reported (Messina et al 2014).…”
Section: Introductionmentioning
confidence: 99%